Synthesizing feminist and post-Keynesian/Kaleckian economics for a purple–green–red transition - Özlem Onaran; Cem Oyvat (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2023)
The aim of this article is to discuss why we should synthesize feminist and post-Keynesian/Kaleckian economics. We answer three related questions. Why does post-Keynesian economics need feminist economics? Why does feminist economics need post-Keynesian macroeconomics? Finally, what is the relevance of synthesizing feminist and post-Keynesian economics for policy analysis in the twenty-first century? We then present a theoretical synthesis model bringing together and extending the existing macroeconomic models in feminist post-Keynesian economics. Finally empirical findings based on this synthesis model are discussed in a policy context.
Keywords: E12; B53; E24; E62; Q54; Q58; 330; feminist economics; post-Keynesian economics; Kaleckian economics; care economy; green economy; employment; gender